Emotional Intelligence in Undergraduate Medical Students: A Qualitative Study Report - Manisha Khadga Yadav (Journal of Development Review, 2025)
This research paper examines the emotional intelligence among undergraduate medical students, highlighting their experiences of stress and emotional management during interactions with their patients and colleagues. Many medical students experience significant emotional strain, often recalling personal and familial hardships while facing patients for the first time, leading to an emotional imbalance. Emotional intelligence, intertwined with factors like age, gender, education, occupation and nationality, emerged as essential for understanding patient emotions and effective care. And, it is more important for those people who belong to the field of medicine, nursing, care-giving, hospitality management, etc. However, this paper focuses on students of medicine, utilizing a snowball sampling method, in which a total of thirteen medical students responded via open-ended interviews. The interview explored respondent’s ideas about emotional awareness, emotional expression, emotional management, and understanding of patients’ emotions. Results reveal that students often struggle with emotional regulation, managing negative feelings primarily in isolation, which may lead to emotional detachment during patient care. The findings suggest that emotional intelligence training is vital for medical curricula to enhance students' coping mechanisms and empathetic skills. The participants also expressed a need to understand patient emotions, recognizing that such insight can facilitate better recovery outcomes. The study underscores the importance of emotional intelligence in medical education, advocating for a curriculum that supports emotional development to mitigate stress and improve overall well-being among future healthcare professionals.